Dark Fandoms: An Introduction and Case Study. Issue 6 (2nd June 2020) - Broll, Ryan
ABSTRACT: There is a deep and persistent cultural fascination with the macabre – public executions, true crime books, slasher films, and sites of violence attract large audiences. Although serial and mass murderers increasingly achieve fame, little attention has focused on their fans. Thus, this paper introduces the concept of dark fandoms, or communities of fans of those who have perpetrated heinous acts, and draws attention to Columbiners as one example of a dark fandom. An analysis of more than 700 threaded discussion posts from an online Reddit community reveals that the Columbiner dark fandom discussed their favorite characters from the shooting, proposed fan theories about the incident, and considered the Columbine shooting's legacy. The implications of these findings for studies of other dark fandoms is discussed.